FEATURES OF THE CLINICAL COURSE OF COVID-19-ASSOCIATED PNEUMONIA IN PATIENTS RECEIVING STATINS - N. M. Seredyuk; O. Z. Skakun (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2022)
Despite the vaccination and the use of specific monoclonal antibodies, COVID-19 is an important medical and social problem. Comorbidities, including hypertension, may worsen the clinical condition in COVID-19 patients. The aim of the study was to determine the features of the clinical course of COVID-19 in patients with hypertension treated with statins. The study includes 29 patients receiving statins in the addition to standard therapy (main group) and 77 patients who received only standard therapy (control group). The sIL-2R level was lower in patients of the main group (3.4 [2.6–4.2] ng/mL) than in patients of the control group (4.7 [3.3–6.8] ng/mL) (p=0.03). There was a tendency to lower frequency of desaturation to the level of <93% during all inpatient stay in patients of the main group (odds ratio = 0.46 [0.19–1.14], p=0.09). Subgroup analysis showed that statins reduced the number of patients who had a decrease in blood oxygen to <93% for inpatient stay among those with ≥65 years by 72.9% (p=0.03), as well as in patients with BMI ≥25.0 kg/m2 by 71.7% (p=0.02). The tendency to reduce the probability of oxygen desaturation to the level of <93% for inpatient stay was in patients with the main group (p=0.07). Some tendency to reduce the likelihood of a severe/critical course of the COVID-19 was observed in patients of the main group with BMI ≥25.0 kg/m2 (p=0.08) and patiens with diabetes mel- litus (p=0.098). Thus, statins improved the clinical condition of the COVID-19 patients, and especially a significant positive effect on the use of statins was observed in patients aged ≥65 years, with BMI ≥25.0 kg/m2 and in patients with diabetes mellitus. Key words: COVID-19, coronavirus disease, statins, hypertension.